The subtle body : the story of yoga in America - Syman, Stefanie (Farrar, Straus and Giroux, 2010)
In "The Subtle Body," Stefanie Syman tells the surprising story of yoga's transformation from a centuries-old spiritual discipline to a multibillion-dollar American industry.